Fall Prevention in a Primary Care Setting: The Effects of a Targeted Complex Exercise Intervention in a Cluster Randomized Trial - Siegrist, Monika (Dtsch Arztebl Int, 2016)
BACKGROUND: Falls and fall-related injuries are common in community-dwelling elderly people. Effective multifactorial fall prevention programs in the primary care setting may be a promising approach to reduce the incidence rate of falls. METHODS: In a cluster randomized trial in 33 general practices 378 people living independently and at high risk of falling (65 to 94 years old; 285 women) were allocated to either a 16 week exercise-based fall prevention program including muscle strengthening and challenging balance training exercises, combined with a 12 week home-based exercise program (222 participants), or to usual care (156 participants). The main outcome was number of falls over a period of 12 months. Secondary outcomes were the number of fall-related injuries, physical function (Timed-Up-and-Go-Test, TUG, Chair-Stand-Test, CST, modified Romberg Test), and fear of falling. RESULTS: In the intervention group (n=222 patients in 17 general practices) 291 falls occurred, compared to 367 falls in the usual care group (n=156 patients in 16 general practices). We observed a lower incidence rate for falls in the intervention group (incidence rate ratio/IRR: 0.54; 95% confidence interval (CI): [0.35; 0.84], p=0.007) and for fall-related injuries (IRR: 0.66; [0.42; 0.94], p=0.033). Additionally, patients in the intervention group showed significant improvements in secondary endpoints (TUG: –2.39 s, [–3.91; –0.87], p=0.014; mRomberg: 1.70 s, [0.35; 3.04], p=0.037; fear of falling: –2.28 points, [–3.87; –0.69], p=0.022) compared to usual care. CONCLUSION: A complex falls prevention program in a primary care setting was effective in reducing falls and fall-related injuries in community dwelling older adults at risk.